Forensic differentiation of Malaysia biodiesel and illicit fuels using GC-FID and GC–MS techniques - Abdull Manap, Mohd Rashidi; Retnam, Ananthy; Abdul Rahman, Norizah; Mohammed, Nurul Ain; Rozlan, Nurul Zulaikha; Sew, Hui Juen; Azis, Ramizah; Hamzah, Noor Hazfalinda; Weller, Philipp (Elsevier Ltd, 2026)
Illegal, unreported, and unregulated (IUU) fishing poses a serious threat to marine biodiversity and economic stability, particularly in coastal nations like Malaysia, where the smuggling of government-subsidized fuel is often linked to IUU activities. This study presents a forensic approach using gas chromatography-flame ionization detection (GC-FID) and gas chromatography-mass spectrometry (GC–MS) to chemically characterize and differentiate between legally distributed Malaysia biodiesel blends (B7 and B10) and illicit fuels seized from vessels involved in maritime violations. A total of 29 fuel samples from detained vessels in Kuala Terengganu and Mersing were compared with 20 reference biodiesel samples from major Malaysia fuel brands. GC-FID revealed hydrocarbon ranges of C10–C29 in biodiesel, with additional FAME peaks near n-C19 and n-C21, while IUU fuels showed wider ranges (C10–C33) but no FAMEs. GC–MS confirmed key biomarkers—bicyclic sesquiterpanes, adamantanes, isoprenoids, PAHs, and FAMEs—highlighting methyl palmitate (C16:0) and methyl oleate (C18:1) as diagnostic of biodiesel. Multivariate analyses (HCA and PCA) further separated B7, B10 and IUU samples, with subtle differences between B7 and B10 attributed to feedstock or blending variation. This study is the first to combine GC-FID, GC–MS, and chemometric analyses (PCA and HCA) into a forensic framework for differentiating Malaysian biodiesel blends (B7, B10) from illicit maritime fuels. By leveraging diagnostic biomarkers beyond FAMEs, the approach enables robust classification and provenance analysis. This integrated strategy provides evidential value for maritime law enforcement, advancing fuel forensics in Southeast Asia. These findings display the utility of chromatographic techniques in maritime law enforcement, enabling fuel source attribution and supporting legal proceedings. Despite promising results, limitations such as restricted sample coverage, lack of replicate analysis, and absence of a chromatographic fingerprint database highlight the need for further validation. The study advocates for the development of an integrated GC-based forensic framework to enhance Malaysia's capability in combatting fuel smuggling and IUU fishing activities.